Long term stability and interaction with epithelial cells of freeze-dried pH-responsive liposomes functionalized with cholesterol-poly(acrylic acid) - Simões, M. G. (2018)
Liposomes are exceptional carriers for therapeutic drug delivery. However, they generally suffer from poor cell penetration, low half-life in bloodstream and loss of functionality during storage. To overcome these problems some strategies can be applied, such as functionalization with polymers and the use of protective molecules during dehydration processes. This work reports a complete study about the stability, including freeze-drying in the presence of trehalose, storage and internalization into HEp-2 cells, of stable formulations of pH sensitive polymer-liposome complexes (PLC) composed of soybean lecithin and crosslinked/non-crosslinked poly(acrylic acid) with a cholesterol end-group (CHO-PAA). The results showed that the average hydrodynamic particle size of the complexes persisted unaffected for approximately 75 days after freeze-drying in the presence of 10% w/v trehalose. The efficiency of calcein encapsulation and release profiles in physiologic conditions exhibited no significant alterations when stored for 0 and 1 month, and for 2 and 3 months of storage the calcein release increased with time. The stored complexes were efficiently uptaken into HEp-2-cells, as determined by confocal microscopy. In all cases, the percentage of viable cells was above 90%, as determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, indicating no potential toxicity. Finally, transepithelial transport assays demonstrated that both fresh and 2 months-stored complexes could transport their calcein content through HEp-2 monolayers over time.